(untitled) (The Conference Hub, 2025)
This paper examines the historical development of two leading international financial centers (IFCs), New York and London, and outlines how Uzbekistan might adapt selected practices to strengthen its own financial ecosystem. In today’s globalized economy, IFCs managing capital flows, investments, banking, and stock markets are vital assets for national and global growth. New York and London hold a distinctive role as hubs that stimulate trade, investment, and innovation, thereby contributing to worldwide stability. The effectiveness of IFCs depends on infrastructure, legal frameworks, and skilled professionals. The New York Stock Exchange and London’s financial district, as the “hearts” of global markets, provide opportunities for corporations and investors, generate employment, and integrate innovative technologies. Beyond finance, they rely on transparency, regulation, stability, and digital leadership to build investor confidence and promote sustainable international cooperation.